Tingkat Pengetahuan Masyarakat Tentang Self Medication Penggunaan Obat Anti Inflamasi Nonsteroid (Oains) Pada Pasien Sakit Gigi Di Apotek Kahuripan Cilacap - Eko Hidayaturrohman Khumaeni; Dyah Ayu Widowati; Dwi Priyo Santoso (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Self-medication is the behavior of people who consume drugs independently based on their diagnosis to treat minor illnesses. Self-medication has several advantages, but self-medication also has risks if done incorrectly. In the 2019 national socio-economic survey in Indonesia, it was found that 71.46% of people carried out self-medication, while only 28.54% went to see a doctor. Limited public knowledge about the use of drugs can lead to errors in treatment. The aim of the study was to determine the effect of the relationship between the level of public knowledge and the use of NSAIDs in toothache patients, and to know the description of public knowledge about the use of NSAIDs in toothache patients. This type of research is analytic correlation research with a cross-sectional study design method which was carried out without any intervention or treatment during the study and data collection was carried out once at a time. The research was conducted at the Kahuripan Cilacap Pharmacy. The level of patient self-medication knowledge influences the patient's self-medication behavior. The results show the level of public knowledge in Kuripan Village, Kabupaten Cilacap based on the question about NSAID self-medication was classified as sufficient knowledge with a total of 75 respondents (54%), a lack of knowledge with a total of 52 respondents (37.4%), and a good level of knowledge with a total of 12 respondents (8.6%). The study findings show the level of knowledge in self-medication using NSAIDs in patients at the Kahuripan Pharmacy, Kabupaten Cilacap belongs to the level of sufficient knowledge.